Application of laser technology in the removal of unwanted hair - Wioleta Jankowiak; Edyta Bartoszewicz; Weronika Jereczek (Our Dermatology Online, 2023)
Laser hair removal requires knowledge of their physical basis and the biophysical phenomena they induce in the skin. Lasers differ in such categories as wavelenght, Energy density and laser beam size. These elements are important while selecting the right device for the skin type and individual characteristics of the patient. Knowledge of the physiology of hair and the photothermolysis that occurs during epilation, allows the treatment to be carried out correctly and safely, and the entire proces of hair elimination to be controlled. Previous studies indicate a numer of factors that determine the effectiveness of the procedure, including the parameters of the device or skin type. Despite the high degree of safety and effectiveness of the laser epilation procedure, it is also pointed out that there are undesirable consequences that may appear in response to the effects of laser light.